Razonamiento lógico-matemático en las escuelas - Rocío Berrocal-Mora; Oscar Gómez-Berrocal (Revista Electrónica Educare)
Based on the results of their licenciatura thesis "Methodological strategy for the development of logical-mathematical reasoning”, presented to the Division of Rural Education, CIDE the authors explain the six phases developed by the German mathematician, Zotan Pier Dienes. They propose an alternative strategy to deepen and accomplish a better achievement in the development of factual thinking.